Penerapan Model Pembelajaran Problem Based Learning berbasis Padlet dalam Meningkatkan Minat Belajar dan Hasil Belajar Kognitif Siswa - Syarofah, Adif Fatus; Ferina Agustini; Moch. Anshori (Pascasarjana Universitas PGRI Semarang, 2024)
Student learning outcomes can be influenced by internal and external factors, one of the internal factors is student interest in learning. This research aims to analyze the application of padlet-based problem based learning in increasing learning interest and cognitive learning outcomes of class X-12 students at SMA Negeri 3 Semarang. The research method uses classroom action research which is carried out over two cycles with each cycle consisting of three stages, namely planning, implementation and observation and reflection. Data collection techniques include learning interest questionnaires given to students, observation and interview sheets as well as formative scores in the form of post-tests. Based on the data analysis that has been carried out, the results obtained are an increase in student interest in learning in cycle 1 by 71% to 82% in cycle 2 which is included in the high category. Students' cognitive learning outcomes also increased from an average of 77 in cycle 1 to 82 in cycle 2 with one student who did not complete the KKTP, so it can be concluded that the application of padlet-based problem based learning can increase students' interest and cognitive learning outcomes.